Carrageenan promotes plant growth in banana via enhancement of cellular metabolism, nutrient uptake, and cellular homeostasis - Kah, Lok Thye; Wan Abdullah, Wan Muhamad Asrul Nizam; Balia Yusof, Zetty Norhana; Chien, Yeong Wee; Ong, Janna Abdullah; Jiun, Yan Loh; Wan, Hee Cheng; Lamasudin, Dhilia Udie; Kok, Song Lai (Springer Nature, 2022)
Banana (Musa acuminata) is an important fruit crop and source of income for various countries, including Malaysia. To date, current agrochemical practice has become a disputable issue due to its detrimental effect on the environment. λ-carrageenan, a natural polysaccharide extracted from edible red seaweed, has been claimed to be a potential plant growth stimulator. Hence, the present study investigates the effects of λ-carrageenan on plant growth using Musa acuminata cv. Berangan (AAA). Vegetative growth such as plant height, root length, pseudostem diameter, and fresh weight was improved significantly in λ-carrageenan-treated banana plants at an optimum concentration of 750 ppm. Enhancement of root structure was also observed in optimum λ-carrageenan treatment, facilitating nutrients uptake in banana plants. Further biochemical assays and gene expression analysis revealed that the increment in growth performance was consistent with the increase of chlorophyll content, protein content, and phenolic content, suggesting that λ-carrageenan increases photosynthesis rate, protein biosynthesis, and secondary metabolites biosynthesis which eventually stimulate growth. Besides, λ-carrageenan at optimum concentration also increased catalase and peroxidase activities, which led to a significant reduction in hydrogen peroxide and malondialdehyde, maintaining cellular homeostasis in banana plants. Altogether, λ-carrageenan at optimum concentration improves the growth of banana plants via inducing metabolic processes, enhancing nutrient uptake, and regulation of cell homeostasis. Further investigations are needed to evaluate the effectiveness of λ-carrageenan on banana plants under field conditions.